Agathis trees of Patagonia's Cretaceous‐Paleogene death landscapes and their evolutionary significance. Issue 8 (3rd August 2018) - Escapa, Ignacio H.; Iglesias, Ari; Wilf, Peter; Catalano, Santiago A.; Caraballo‐Ortiz, Marcos A.; Rubén Cúneo, N.
Abstract : Premise of the Study: The fossil record of Agathis historically has been restricted to Australasia. Recently described fossils from the Eocene of Patagonian Argentina showed a broader distribution than found previously, which is reinforced here with a new early Paleocene Agathis species from Patagonia. No previous phylogenetic analyses have included fossil Agathis species. Methods: We describe macrofossils from Patagonia of Agathis vegetative and reproductive organs from the early Danian, as well as leaves with Agathis affinities from the latest Maastrichtian. A total evidence phylogenetic analysis is performed, including the new Danian species together with other fossil species having agathioid affinities. Key Results: Early Danian Agathis immortalis sp. nov. is the oldest definite occurrence of Agathis and one of the most complete Agathis species in the fossil record. Leafy twigs, leaves, pollen cones, pollen, ovuliferous complexes, and seeds show features that are extremely similar to the living genus. Dilwynites pollen grains, associated today with both Wollemia and Agathis and known since the Turonian, were found in situ within the pollen cones. Conclusions: Agathis was present in Patagonia ca. 2 million years after the K‐Pg boundary, and the putative latest Cretaceous fossils suggest that the genus survived the K–Pg extinction. Agathis immortalis sp nov. is recovered in a stem position for the genus, while A. zamunerae (Eocene, Patagonia) is recovered as part of the crown. A Mesozoic divergence for the Araucariaceae crown group, previously challenged by molecular divergence estimates, is supported by the combined phylogenetic analyses including the fossil taxa.